2019
DOI: 10.1097/aog.0000000000003468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shared Decision Making on Opioid Prescribing After Hysterectomy

Abstract: OBJECTIVE: To evaluate the effects of shared decision making using a simple decision aid for opioid prescribing after hysterectomy. METHODS: We conducted a prospective quality initiative study including all patients undergoing hysterectomy for benign, nonobstetric indications between March 1, 2018, and July 31, 2018, at our academic institution. Using a visual decision aid, patients received uniform education regarding postoperative pain management. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…In patients undergoing hysterectomies, those who participated in a preoperative patient education program consumed significantly fewer oral morphine equivalents at the time of discharge with no significant change in patient satisfaction or number of refills. This education program included a discussion of pain expectations and information regarding the mean number of opioids used by a similar cohort, and patients were then able to choose the number of opioids prescribed at discharge [ 19 ]. Similarly, a recently published randomized controlled trial examining the effect of opioid-related preoperative patient education on post-discharge opioid consumption in patients undergoing arthroscopic rotator cuff repair reported that preoperative patient education significantly decreased the number of opioid pills consumed at 3 months after surgery.…”
Section: Preoperative Interventionsmentioning
confidence: 99%
“…In patients undergoing hysterectomies, those who participated in a preoperative patient education program consumed significantly fewer oral morphine equivalents at the time of discharge with no significant change in patient satisfaction or number of refills. This education program included a discussion of pain expectations and information regarding the mean number of opioids used by a similar cohort, and patients were then able to choose the number of opioids prescribed at discharge [ 19 ]. Similarly, a recently published randomized controlled trial examining the effect of opioid-related preoperative patient education on post-discharge opioid consumption in patients undergoing arthroscopic rotator cuff repair reported that preoperative patient education significantly decreased the number of opioid pills consumed at 3 months after surgery.…”
Section: Preoperative Interventionsmentioning
confidence: 99%
“…During recent years, reports of differing strategies to decrease opioid Flowchart of patients included in the new departmental opioid-prescribing policy analysis before and after its implementation MATERNAL Original Research use for acute pain (ie, postoperative period) have been published, such as shared decision-making models for opioid prescriptions 8,9 and routine use of specialized inpatient order sets. 5,10 Specifically, for vaginal deliveries, recent work has highlighted a successful initiative to decrease inpatient opioid use.…”
Section: Resultsmentioning
confidence: 99%
“…42 Shared-decision making can further decrease opioid prescribing, without reducing patient satisfaction or postoperative pain control. 43 Tapentadol (a relatively new medication) may become an alternative to oxycodone. Some studies have shown similar analgesic efficacy to oxycodone, with less nausea and constipation.…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…Individual variability in patients’ postoperative opioid consumption means that clinicians should consider patient factors such as preoperative opioid use and history of endometriosis 42 . Shared‐decision making can further decrease opioid prescribing, without reducing patient satisfaction or postoperative pain control 43 …”
Section: Postoperative: In the Recovery Bay And/or Wardmentioning
confidence: 99%